Putative direct and indirect Wnt targets identified through consistent gene expression changes in APC-mutant intestinal adenomas from humans and mice. - Segditsas, S; Sieber, O; Deheragoda, M; East, P; Rowan, A; Jeffery, R; Nye, E; Clark, S; Spencer-Dene, B; Stamp, G; Poulsom, R; Suraweera, N; et al. (2008)
In order to identify new genes with differential expression in early intestinal tumours, we performed mRNA (messenger ribonucleic acid) expression profiling of 16 human and 63 mouse adenomas. All individuals had germline APC mutations to ensure that tumorigenesis was driven by 'second hits' at APC. Using stringent filtering to identify changes consistent between humans and mice, we identified 60 genes up-regulated and 151 down-regulated in tumours. For 22 selected genes--including known Wnt targets--expression differences were confirmed by qRT-PCR (quantitative reverse transcription polymerase chain reaction). Most, but not all, differences were also present in colorectal carcinomas. In situ analysis showed a complex picture. Expression of up-regulated genes in adenomas was usually uniform/diffuse (e.g. ITGA6) or prominent in the tumour core (e.g. LGR5); in normal tissue, these genes were expressed at crypt bases or the transit amplifying zone. Down-regulated genes were often undetectable in adenomas, but in normal tissue were expressed in mesenchyme (e.g. GREM1/2) or differentiated cells towards crypt tops (e.g. SGK1). In silico analysis of TCF4-binding motifs showed that some of our genes were probably direct Wnt targets. Previous studies, mostly focused on human tumours, showed partial overlap with our 'expression signature', but 37 genes were unique to our study, including TACSTD2, SEMA3F, HOXA9 and IER3 (up-regulated), and TAGLN, GREM1, GREM2, MAB21L2 and RARRES2 (down-regulated). Combined analysis of our and published human data identified additional genes differentially expressed in adenomas, including decreased BMPs (bone morphogenetic proteins) and increased BUB1/BUB1B. Several of the newly identified, differentially expressed genes represent potential diagnostic or therapeutic targets for intestinal tumours.